The potential use of oil palm frond mulch treated with imazethapyr for weed control in Malaysian coconut plantation - Dilipkumar Masilamany,; Mazira Che Mat,; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2017)
Introduction of new weed management strategy for coconut plantation in Malaysia is essential since the current weed control methods are less effective and highly herbicide dependent, thus leading to development of herbicide resistance in weeds as well as environmental and human health concerns. Thus, the present study aimed to evaluate the phytotoxic effects of oil palm frond mulch treated with imazethapyr at a reduced rate on weed emergence and growth. The results of glasshouse experiments have shown that imazethapyr at 12 g a.i. ha-1 in combination with oil palm residues of leaflet (OPL), rachis (OPR) or frond (OPF) at rates of 1.4-1.8 t ha-1 inhibited Eleusine indica emergence and growth by 90-100%, implying that imazethapyr is compatible with oil palm residue mulches. In the field experiment, hand weeding followed by OPF at 3.4 t ha-1 treated with imazethapyr at 24 g a.i. ha-1 have demonstrated excellent control of Mikania micrantha, Asystasia gangetica, Phyllanthus amarus, Panicum sp. and Echinochloa colona by reducing their total dry weight up to 95% at three months after treatment. The present results suggested that the integration of chemical, physical and mechanical methods can provide effective weed control in the coconut plantation for months.